'Inequality in equality' in the European Union equality directives: A friend or a foe of more systematized relationships between the protected grounds?. (December 2015) - Neuvonen, Päivi Johanna
The multi-ground anti-discrimination regimes, such as the one adopted in the European Union (EU) equality directives, have to reconcile the potentially conflicting aims of 'integration' and 'diversity' between the multiple protected grounds. A more systematic account of how the different grounds of prohibited discrimination relate to one another is needed to explain the differing scope of protection in relation to different grounds as well as to solve potential conflicts between the protected grounds. This article first briefly reiterates how the issue of 'inequality in equality' emerges from the EU equality directives. It will then move on to examine how these so-called 'equality hierarchies' can be understood in the light of the contemporary discrimination theory. From this theoretical analysis follows the argument that the relationships between different grounds of prohibited discrimination are shaped by the complexity of social identities that underlie the protected grounds. Any attempt to systematize the relationships between the protected grounds therefore stands or falls depending on how well it succeeds in taking into account this complexity. Finally, the article outlines how the idea of subjectivity as 'identity through agency' can respond to the complexity of identity formation and provide a much-needed substantive standard for normative ordering between the protected grounds in multidimensional anti-discrimination law.